Apis mellifera (Hymenoptera, Apini) Ovary Development in Queens and in Workers from Queenright and Queenless Colonies - Patricio, K. [UNESP]; Da Cruz-Landim, C. [UNESP] (My University, 2003)
A morphological study of the development of the ovaries in workers from queenright and queenless colonies and queens of Apis mellifera is presented and discussed. The mating stimulates the ovary development and the egg-laying. Mating prevention or egg laying prevention provokes reabsorption in the queens ovaries, characteristic of the queen stage or ovariole development. Ovary development was observed in queenless and in queenright colonies but the queen's presence, the worker's age and the type of tasks done by them interfere with their development.
Keywords: Apis mellifera; Development; Ovary; Queen; Worker; Apini; Hymenoptera; Invertebrata